Variable λ-Central Morrey Space Estimates for the Fractional Hardy Operators and Commutators - Amjad Hussain; Muhammad Asim; Fahd Jarad (Journal of Mathematics)
This paper aims to show that the fractional Hardy operator and its adjoint operator are bounded on central Morrey space with variable exponent. Similar results for their commutators are obtained when the symbol functions belong to λ-central bounded mean oscillation (λ-central BMO) space with variable exponent.